Palaeoenvironmental changes since the Last Glacial Maximum: patterns, timing and dynamics throughout South America - Fontana, Sonia L. (2012)
The vast diversity of present vegetation and environments that occur throughout South America (12°N to 56°S) is the result of diverse processes that have been operating and interacting at different spatial and temporal scales. Global factors, such as the concentration of CO2 in the atmosphere, may have been significant for high altitude vegetation during times of lower abundance, while lower sea levels of glacial stages potentially opened areas of continental shelf for colonisation during a substantial portion of the Quaternary. Latitudinal variation in orbital forcing has operated on a regional scale. The pace of climate change in the tropics is dominated by precessional oscillations of c. 20 kyr, while the high latitudes of the south are dominated by obliquity oscillations of c. 40 kyr. In particular, seasonal insolation changes forced by precessional oscillations must have had important consequences for the distribution limits of species, with potentially different effects depending on the latitude. The availability of taxa, altitude and human impact, among other events, have locally influenced the environments. Disentangling the different forcing factors of environmental change that operate on different timescales, and understanding the underlying mechanisms leads to considerable challenges for palaeoecologists. The papers in this Special Issue present a selection of palaeoecological studies throughout South America on vegetation changes and other aspects of the environment, providing a window on the possible complexity of the nature of transitions and timings that are potentially available.